Peran Pemerintah Desa Dalam Meminimalisir Risiko Bencana Alam Di Wilayah Pesisir (Studi Pada Desa Tombawatu) - Wa Ode Srijuna Ramayana; L.M.Iradat Salihin; Al Rubayn (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Village governments as the vanguard of regional government should be able to demonstrate the best performance in carrying out government duties and functions. However, the Tombawatu Village Government has not been optimal in carrying out its duties and functions. As a result, there were casualties among the community which could have been anticipated if the village government had played a maximum role in reducing the risk of natural disasters. The problems in this research are analyzed using the concept of roles which are divided into three indicators, namely the role of government as a regulator, the role as a dynamic agent and the role as a facilitator. By using qualitative research methods and data collection techniques through interviews, observation, documentation, and literature studies. The results show that the role of the village government has not been optimal in minimizing disaster risks in Tombawatu Village. The direction and development policies of Tombawatu Village have not identified various internal and external organizational factors and have not been included in village regulations, the village government has not been able to mobilize the community to maintain various facilities that have been attempted by the village government, the formation of a disaster volunteer team has not been supported by the village revenue and expenditure budget. To overcome this, the village government needs to collaborate with universities in formulating development directions and policies, motivating and mobilizing the community to participate in maintaining existing facilities through active community participation in every stage of development, preparing regulations that support development directions and policies based on internal and external factors of the organization.